Childhood Adversity and Affective Touch Perception: A Comparison of United Kingdom Care Leavers and Non-care Leavers - Devine, Shaunna L.; Walker, Susannah C.; Makdani, Adarsh; Stockton, Elizabeth R.; McFarquhar, Martyn J.; McGlone, Francis P.; Trotter, Paula D. (Frontiers in Psychology, 2020)
In the United Kingdom, the most common reasons for a child to come under the care of social services are neglect and abuse. Such early childhood adversity is a risk factor for social-isolation and poor mental health in adulthood. Touch is a key channel for nurturing interactions, and previous studies have shown links between early somatosensory input, experience dependent neural plasticity, and later life emotional functioning. The aim of the present study was to test the relationship between childhood neglect/abuse and later life experiences, attitudes, and hedonic ratings of affective touch. Here, affective touch is defined as low force, dynamic touch which C-Tactile afferents (CTs) respond optimally to. We hypothesized that a childhood lacking in early nurturing tactile stimulation would be associated with reduced sensitivity to socially relevant affective touch in adulthood. To test this, 19 care leavers (average 9.32 ± 3.70 years in foster care) and 32 non-care leavers were recruited through opportunity sampling (mean age = 21.25 ± 1.74 years). Participants completed a range of psychophysical somatosensory tests. First, they rated the pleasantness of CT-optimal (3 cm/s) and non-CT-optimal (0.3 and 30 cm/s) stroking touch applied to their forearm, both robotically and by an experimenter. They also made vicarious ratings of the anticipated pleasantness of social tactile interactions depicted in a series of videos. Finally, they filled in the Childhood Trauma Questionnaire (CTQ) and the Touch Experiences and Attitudes Questionnaire (TEAQ). As expected, care leavers reported significantly higher levels of childhood trauma than the control group. They also reported significantly lower levels of positive childhood touch compared to non-care leavers, but their attitudes and experiences of current intimate and affiliative touch did not differ. Across all psychophysical tests, care leavers showed specific reduction in sensitivity to the affective value of CT targeted 3 cm/s touch. The results of this study support the hypothesis that a lack of nurturing touch in early developmental periods leads to blunted sensitivity to the specific social value of affective touch. Future research should investigate the neural and physiological mechanisms underlying the observed effect.